Efeito do tipo de alimento no desempenho produtivo de juvenis de acará-bandeira (Pterophyllum scalare) - Takahashi, Leonardo Susumu [UNESP]; da Silva, Thiago Verzegnossi [UNESP]; Fernandes, João Batista Kochenborger [UNESP]; Biller, Jaqueline Dalbello [UNESP]; de Sandre, Lidiane Cristina Gonçalves [UNESP] (My University, 2010)
This study aimed to evaluate the effect of food type on growth performance and water quality of angelfish juvenile. A total of 168 angelfish Pterophyllum scalare var. marble (wi = 151.3 ± 37.9 mg e li = 2.2 ± 0.07 cm) were distributed in 12 aquaria 14 L (1.0 fish L-1). The experiment was conducted in a complete randomized design with three treatments and four replicates. Foods evaluated were: Artemia nauplii, commercial flakes diet and commercial powder diet. Fish weight and length were recorded in the beginning and the end of 60 experimental days. Water temperature, issolved oxygen, pH and total ammonia were monitored during experiment. Best averages of final weight, final length, weight gain and condition factor were observed on fish fed powder diet. Specific growth rate, weight uniformity and survival were not influenced (p >0.05) by food type. Just on length uniformity fish fed Artemia showed better averages than fish fed flakes diet and powder diet. Foods evaluated did not influenced (p >0.05) on water quality parameters. In conclusion, for juvenile angelfish, the food type influences growth performance without affect water quality parameters. Powder diet resulted in better growth performance.
Effect of food type on growth performance of angelfish juvenile (Pterophyllum scalare)
Keywords: Artemia; Feeding; Flakes diet; Ornamental fish; Powder diet